1999
DOI: 10.1159/000029671
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Ventral Intermediate Nucleus of the Thalamus for Control of Tremors in Parkinson’s Disease and Essential Tremor

Abstract: The beneficial effects of ventral intermediate nucleus (VIM) stimulation were evaluated in 20 patients with tremor refractory to medical therapy. Thalamic stimulation is a non-ablative procedure which has the advantage of a reversible, non-destructive lesion. Eleven patients [7 with Parkinson’s disease (PD) and 4 with essential tremor (ET)] received unilateral VIM implantation, while 9 patients had staged bilateral VIM implantation (4 with PD, 5 with ET). PD patients showed a significant improvement in contral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 16 publications
1
33
1
3
Order By: Relevance
“…1,9,26,30,35,41 Despite their delivered improvement in tremor, these therapeutic modalities are often accompanied by adverse effects on speech or language. Recently, a meta-analysis demonstrated that speech difficulty occurred in 19.8% of patients after RF thalamotomy and 19.4% after DBS.…”
Section: Neurosurg Focus 44 (2):e8 2018mentioning
confidence: 99%
“…1,9,26,30,35,41 Despite their delivered improvement in tremor, these therapeutic modalities are often accompanied by adverse effects on speech or language. Recently, a meta-analysis demonstrated that speech difficulty occurred in 19.8% of patients after RF thalamotomy and 19.4% after DBS.…”
Section: Neurosurg Focus 44 (2):e8 2018mentioning
confidence: 99%
“…There have been multiple reports of the benefits of DBS of the Vim of the thalamus for the treatment of ET. 7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Table 1 summarizes selected long-term studies of Vim DBS for ET. The first North American multicenter study 11 of unilateral DBS of the thalamus in 29 ET patients demonstrated a significant improvement in contralateral hand tremor of approximately 60% and an improvement of between 43% and 68% in activities of daily living such as writing, drawing and pouring, 3 and 12 months after surgery.…”
Section: Essential Tremormentioning
confidence: 99%
“…DBS is a nonablative alternative to thalamotomy, and involves the insertion of stimulating electrodes into the Vim, which are then connected to an implanted pulse generator. Both RF thalamotomy and DBS are highly effective in treating ET, with tremor control rates approaching 80-90 % [37,38,44,45]. DBS can be performed bilaterally, whereas thalamotomy is typically restricted to one side.…”
Section: Etmentioning
confidence: 99%